2014
DOI: 10.15557/pimr.2014.0026
|View full text |Cite
|
Sign up to set email alerts
|

Syncope in children and adolescents as a sudden, transient, short-term and spontaneously reversible loss of consciousness caused by a decrease in cerebral perfusion

Abstract: Omdlenia są częstym objawem u młodzieży zgłaszającej się do szpitalnych oddziałów ratunkowych. Najczęstszą postacią są omdlenia odruchowe, spowodowane zaburzoną autoregulacją układu krążenia. Na ogół nie stanowią one stanu zagrożenia utraty życia, w odróżnieniu od znacznie rzadszych, lecz niebezpiecznych omdleń kardiogennych, które w pewnych okolicznościach mogą być bardzo groźne -występują one np. w wyniku zaburzeń rytmu serca w zespole Wolffa-Parkinsona--White'a czy wydłużonego odstępu QT, bloków przedsionko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Syncope accounts for 1-6% of hospital admissions and is not easily diagnosed [1]. Most (~75%) cases of syncope in children and adolescents are caused by an abnormal neuroregulation reflex of the cardiovascular system in an otherwise structurally healthy heart, termed vasovagal syncope (VVS) [1][2][3]. VVS can occur from orthostatic stress (e.g., a long-standing vertical position or sudden change in body position) or emotional distress (e.g., pain, fear), and is characterized by the appearance of prodromal symptoms (e.g., vision and hearing disorders, dizziness, excessive sweating, skin paleness, and dyspnea) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Syncope accounts for 1-6% of hospital admissions and is not easily diagnosed [1]. Most (~75%) cases of syncope in children and adolescents are caused by an abnormal neuroregulation reflex of the cardiovascular system in an otherwise structurally healthy heart, termed vasovagal syncope (VVS) [1][2][3]. VVS can occur from orthostatic stress (e.g., a long-standing vertical position or sudden change in body position) or emotional distress (e.g., pain, fear), and is characterized by the appearance of prodromal symptoms (e.g., vision and hearing disorders, dizziness, excessive sweating, skin paleness, and dyspnea) [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the central type of syncope, a vasovagal reaction is triggered in the cerebral cortex and hypothalamus centers by stimulating sensory fibers in specific clinical situations like fear, blood phobia, pain, or strong emotions [1,6,27]. We found that the independent factor predicting the vasovagal syncope was the fear-pain stress emotion, which occurs in negative HUTT (−) (p = 0.016).…”
Section: Discussionmentioning
confidence: 83%
“…Syncope is a common clinical symptom in children and adolescents, which occurs with a frequency of 125 in 10,000 cases with a predominance of females [2,3]. It is estimated that approximately 40% of healthy teenagers have experienced at least one episode of syncope [4][5][6]. The most common loss of consciousness in young people include vasovagal syncope (VVS), known as reflexive, neurogenic, or neurocardiogenic.…”
Section: Introductionmentioning
confidence: 99%